A model of innovation systems with links to creative style and psychological type. (1st January 1999) - Rabson, Jonathan D.; DeMarco, David A.
A method is proposed for understanding the relationships between different types of innovation systems, which are defined as infrastructures for finding, developing, evaluating, and implementing new ideas in an organisation. In parallel to Kirton's theory of creative style, which postulates that a wide range of individual approaches to change may be understood as creative, innovation in organisations is considered to cover a broad spectrum of change-related functions, ranging from continuous improvement of existing capabilities to radical shifts in processes and technologies. Differences among innovation systems are also found to parallel dimensions of psychological type, in much the same way as has been proposed for organisations in general. Empirical relationships between creative style and psychological type are useful in relating these two conceptions of innovation systems. Potential applications include predictions about: (1) the competencies required to run successful innovation systems, (2) the potential clashes between innovation systems and the larger organisation, (3) opportunities to compensate for or capitalise on an organisation's characteristics affecting innovation, and (4) the relevance of various systems to stages of the process from product conceptualisation to commercialisation.